Unlocking Innovation Through Psychological Capital: The Hidden Mediator Between Transformational Leadership and Innovative Work Behavior - Zulhapiz, Mhd. Hanif; Rahayu, Meika Kurnia Puji (Jurnal Manajemen Bisnis, 2025)
Research aims: This study aims to analyze the impact of transformational leadership on innovative work behavior, with proactive personality and psychological capital serving as mediators. This study examines the personnel of PT Pos Indonesia in the special region of Yogyakarta.Design/Methodology/Approach: This research employed a quantitative methodology with a cross-sectional design. Data were obtained from 177 participants utilizing a standardized questionnaire. The data were analyzed using the Structural Equation Modeling (SEM) technique with AMOS software, resulting in a final sample of 170 respondents.Research findings: The findings indicate that transformational leadership and proactive personality significantly influence innovative work behavior. Conversely, psychological capital did not exert a strong direct influence on innovative work behavior. Both proactive personality and psychological capital were found to mediate the association between transformational leadership and innovative work behavior, both independently and sequentially.Theoretical Contribution/Originality: This study enhances the current literature by validating the mediating effects of proactive personality and psychological capital in the association between transformationaI Ieadership and innovative work behavior. The incorporation of these mediators offers novel insights into the mechanisms that propel innovative work behavior.Practitioners/Policy Implications: In terms of management practice, PT Pos Indonesia and similar organizations are encouraged to adopt transformational leadership styles that empower employees and encourage proactivity. In addition, initiatives should be implemented to enhance employees' psychological capital through a supportive work environment to maximize innovation potential.Research Limitations/Implications: This study's weakness is the comparatively low Average Variance Extracted (AVE) value, signifying the construct's restricted capacity to account for the variance of its indicators. The hypothesis positing that psychological capital influences innovative work behavior is rejected.